Evaluation of production cross-sections for 61Cu non-standard PET radionuclide via light-ion-induced nuclear reactions on Co, Ni, Zn targets - Ali, Samer K.I.; Khandaker, Mayeen Uddin; Dababneh, Saed; Kassim, Hasan Abu (Elsevier, 2018)
Production cross-sections of 61Cu, a promising radionuclide for PET imaging applications, were evaluated for the light-ion-induced nuclear reactions on Co, Ni, Zn targets. Simultaneous Evaluation on KALMAN (SOK) code combined with least squares concept was used to obtain the evaluated data together with covariances. The various production routes of 61Cu were compared, and recommended excitation functions were derived using a well-defined statistical procedure. The evaluated data were also compared with the predictions of the nuclear reaction model codes TALYS and EMPIRE, and found a partial agreement among them. This study indicates that the 60Ni(d,n)61Cu reaction is the method of choice for 61Cu production; however, the 58Ni(α,p)61Cu and 59Co(α,2n)61Cu reactions also appears to have great potential.